The Concept of Mazmumah Morality in Islamic Religious Education (A Study of the Book Hidayah al-Salikīn) - Soleh, Warissuddin; Vahlepi, Sahrizal; Jamil, Helmun (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The direction of education in Islam is to give birth to human beings Insan Kamil. Insan Kamil is a human being who has noble morals and avoids mazmumah morals. The urgency of this research is to formulate the concept of mazmumah morals so that it is easier to make references in recognizing mazmumah morals. This research uses the book Hidayah al-Salikin fi Suluki Maslak al-Muttaqin by Abdus Samad al-Palimbani as the object of study. The focus of the research is the fourth chapter with the title Ijtinab al-Ma'ashi al-Bathinah. The research approach is qualitative with library research methods. The data analysis technique uses the Miles and Huberman data analysis model. The results of the research were that ten mazmumah morals were identified which were very suitable to be used as a formulation of the concept of mazmumah morals in Islamic religious education. The ten mazmumah morals put forward in the book are Syarh al-Tha'am, Syarh al-Kalam, Ghadhab, Hasad, Bukhul/Hubbulmal, Hubbuljah, Hubbu al-Dunya, Takabbur, 'Ujub, and Riya.